Mr. Popper's penguins - Atwater, Richard; Atwater, Florence; Lawson, Robert, 1892-1957 (New York : Little, Brown and Co. Books for Young Readers, 2009)
The unexpected delivery of a large crate containing an Antarctic penguin changes the life and fortunes of Mr. Popper, a house painter obsessed by dreams of the Polar regions.
Elem. School Library Collection.
Newbery Medal/Honor.
Wilson's Children.
Book Links (A.L.A.), November 2006.
Booklist, April 1995.
Child Study Children's Book Committee, May 2005.
Keywords: Penguins -- Juvenile fiction; Humorous stories; Penguins -- Fiction; Humorous fiction; Penguins -- Fiction; Humorous fiction